The Adhesive Strength of Epoxy/Sol-Gel Materials Modified by Various Ratio of γ-Al2O3 Nanoparticles - Ali, Balhassn; May, Mousa; Wang, Heming; Akid, Robert (Journal of Coating Science and Technology, 2018)
In this study, the use of sol-gel/epoxy adhesive based on the combination of organic and inorganic components within the adhesive matrix have been studied. The combination of different amounts of ᵞ-Al2O3 nano-particles to the adhesive matrix was evaluated. Mild steel specimens were prepared for lap joints, which were cured in an oven at 200°C for 16 hours. The bond strength of the sol-gel/epoxy matrix was investigated using a universal tensile test machine. The presence of Al-OH and/or Si-OH bonds increases causing an increase in the strength of the bulk material. This process is seen through the appearance of an absorption peak shoulder which appears in the range of 1088 to1100 cm-1 which corresponds to Al-O-Si or Si-O-Si. The maximum adhesive strength of composite sol-gel/epoxy adhesive recorded was 23±0.4 MPa. This was obtained when small amounts of γ-Al2O3 nano-particles (4.0 wt%), were incorporated within the matrix. However, as the level of these inorganic materials in the adhesive matrix increased further, the adhesive shear strength gradually decreased. At a high ratio of γ-Al2O3 particles, poor interfacial bonding or adhesion between the filler and the adhesive matrix is recorded. Scanning Electron Microscopy (SEM) is used to investigate the fracture surface with 4.0 wt% γ-Al2O3, the scanning shows a very small distance of cracks, suggesting the material may act as a barrier to crack propagation and thus increases the energy required for fracture.